Sense of Belonging as Experienced in Recovery from Serious Mental Illness: An Integrative Review - Carvalho, Bárbara Toledo; dos Santos, Caroline; Brisola, Elizabeth B V; Reis, Graziela; Bellamy, Chyrell; Costa, Mark (Journal of Recovery in Mental Health, 2026)
Objectives: The desire to belong is a fundamental aspect of human nature that drives behavior and decision-making. Belonging is not only a need but also a powerful source of motivation. This review aims to contribute to the knowledge regarding recovery from serious mental illness (SMI) and the sense of belonging, by describing how studies understand and incorporate the concept of sense of belonging in mental health practices related to recovery. This topic is important for practitioners, policymakers, people with lived experience, their supporters, and the population in general, as understanding and addressing a sense of belonging should be taken into consideration when effectively supporting and promoting the wellbeing of people with SMI.Research Design and Methods: This integrative review screened peer-reviewed articles from the past 10 years that addressed the sense of belonging involving adult populations experiencing mental suffering.Results: The final sample included 23 empirical studies. These studies revealed the sense of belonging as an experiential, personal, and relational experience involving the following themes: “I can be myself”, “I am a part of the pie”, "I am wanted”, “It’s a mutual thing”, and “There’s trust”.Conclusions: This review emphasizes the important role that a sense of belonging plays in the recovery process, highlighting that inclusion alone is insufficient without a sense of meaningful, reciprocal connections that foster trust. The findings call for further research across disciplines and communities, aiming to genuinely support and embrace people living with SMI.